2018
DOI: 10.1016/j.celrep.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocytes in the Mouse Corpus Callosum Maintain Axonal Function by Delivery of Glucose

Abstract: In the optic nerve, oligodendrocytes maintain axonal function by supplying lactate as an energy substrate. Here, we report that, in acute brain slices of the mouse corpus callosum, exogenous glucose deprivation (EGD) abolished compound action potentials (CAPs), which neither lactate nor pyruvate could prevent. Loading an oligodendrocyte with 20 mM glucose using a patch pipette prevented EGD-mediated CAP reduction in about 70% of experiments. Loading oligodendrocytes with lactate rescued CAPs less efficiently t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 41 publications
3
101
0
Order By: Relevance
“…The recent biosensor experiments are the most direct investigation of the cellular site of aerobic glycolysis in stimulated brain, and they argue strongly that stimulated neurons rely not on astrocytically derived lactate but rather on their own ability to perform glycolysis. Further investigation is needed to learn whether similar results are observed in dendritic or presynaptic compartments of neurons, or in axons, particularly those in white matter that are surrounded by myelin and seem quite likely to rely on surrounding glial cells (oligodendrocytes) for metabolic support (Meyer et al, ; Saab et al, ; Trevisiol et al, ). Moreover, there is evidence that stimulated astrocytes also increase glucose utilization (Chuquet, Quilichini, Nimchinsky, & Buzsáki, ; Loaiza, Porras, & Barros, ) and NADH CYT (Köhler, Winkler, Sicker, & Hirrlinger, ), in support of the possibility of an ANLS.…”
Section: Changes Of Nadhcyt Upon Neuronal Stimulation Results From Glymentioning
confidence: 93%
“…The recent biosensor experiments are the most direct investigation of the cellular site of aerobic glycolysis in stimulated brain, and they argue strongly that stimulated neurons rely not on astrocytically derived lactate but rather on their own ability to perform glycolysis. Further investigation is needed to learn whether similar results are observed in dendritic or presynaptic compartments of neurons, or in axons, particularly those in white matter that are surrounded by myelin and seem quite likely to rely on surrounding glial cells (oligodendrocytes) for metabolic support (Meyer et al, ; Saab et al, ; Trevisiol et al, ). Moreover, there is evidence that stimulated astrocytes also increase glucose utilization (Chuquet, Quilichini, Nimchinsky, & Buzsáki, ; Loaiza, Porras, & Barros, ) and NADH CYT (Köhler, Winkler, Sicker, & Hirrlinger, ), in support of the possibility of an ANLS.…”
Section: Changes Of Nadhcyt Upon Neuronal Stimulation Results From Glymentioning
confidence: 93%
“…Preformed Tau-1N3R fibrils (hereafter referred to as Fib-Tau) were labeled with ATTO-550 dye and fragmented (see Materials and Methods and Appendix Figs S1, and S2A and B). The corpus callosum is rich in oligodendrocytes and myelinated axons facilitating communication between the two hemispheres of the brain (Meyer et al, 2018). Mice were sacrificed 8 or 24 h after injection.…”
Section: Resultsmentioning
confidence: 99%
“…Publications from our lab and others showed that oligodendrocyte-derived lactate is important for supporting axons (Nave, 2010; Funfschilling et al, 2012; Lee et al, 2012; Meyer et al, 2018). In Dr. Nave’s publication, disrupting oligodendrocyte mitochondria led to increased extracellular lactate in the presence of anesthesia that quickly fell after reversal of anesthesia, presumably due to uptake of lactate into metabolically active neurons (Funfschilling et al, 2012).…”
Section: Fuels To Neural Cells: Glucose Its “By-product” Lactate Anmentioning
confidence: 91%
“…In our publication, which will be discussed in greater detail below in section on transporters, axon degeneration or neuron loss was observed in mice and spinal cord organotypic cultures with global or oligodendrocytespecific knockdown of lactate transporters (Lee et al, 2012). A recent study demonstrates that combined blockade of oligodendroglial lactate and glucose export via inhibition of lactate transporters MCT1/2 and glucose transporter GLUT1 completely abolishes oligodendroglial support to axons during aglycaemia (Meyer et al, 2018). Additionally, satellite gliocytes surrounding neurons in cranial cervical sympathetic ganglion (CCSG) are reported to produce significantly more lactate than neurons, suggesting that CCSG, like the brain, develops a gradient for lactate shuttle between sympathetic neurons and surrounding satellite gliocytes (Gorelikov and Savel’ev, 2008).…”
Section: Fuels To Neural Cells: Glucose Its “By-product” Lactate Anmentioning
confidence: 99%